Effects of esketamine on postoperative rebound pain in patients undergoing unilateral total knee arthroplasty: a single-center, randomized, double-blind, placebo-controlled trial protocol - Zhu, Youzhuang; Li, Qun; Liu, Guilin; Sheng, Fang; Zhang, Xiaotian; Jiang, Lili; Li, Shaona; He, Jianshuai; Zou, Zhijin; Zhang, Baobo; Wang, Changyao; Jiang, Xin; et al. (Frontiers in Neurology, 2023)
Introduction Rebound pain, transient and acute postoperative pain after the disappearance of regional block anesthesia, has been a concern in recent years. Insufficient preemptive analgesia and hyperalgesia induced by regional block are the main mechanisms. At present, the evidence for the treatment of rebound pain is limited. The esketamine, as an antagonist of the N-methyl-D-aspartate receptor, has been proven to prevent hyperalgesia. Therefore, this trial aims to evaluate the impact of esketamine on postoperative rebound pain in patients undergoing total knee arthroplasty. Methods/design This study is a single-center, prospective, double-blind, randomized, placebo-controlled trial. Participants who plan to undergo total knee arthroplasty will be randomly assigned to the esketamine group (N = 178) and placebo group (N = 178) in a ratio of 1:1. This trial aims to evaluate the impact of esketamine on postoperative rebound pain in patients undergoing total knee arthroplasty. The primary outcome of this trial is the incidence of rebound pain within 12 h after the operation in the esketamine group and the placebo group. The secondary outcome will be to compare (1) the incidence of rebound pain 24 h after the operation; (2) the time to enter the pain cycle for the first time within 24 h after the procedure; (3) the first time of rebound pain occurred within 24 h after surgery; (4) the modified rebound pain score; (5) NRS score under rest and exercise at different time points; (6) the cumulative opioid consumption at different time points; (7) patient’s prognosis and knee joint function evaluation; (8) blood glucose and cortisol concentration; (9) patient’s satisfaction score; (10) adverse reactions and adverse events. Discussion The effect of ketamine on preventing postoperative rebound pain is contradictory and uncertain. The affinity of esketamine to the N-methyl-D-aspartate receptor is about four times higher than levo-ketamine, the analgesic effect is 3 times higher than levo-ketamine, and there are fewer adverse mental reactions. To our knowledge, there is no randomized controlled trial to verify the impact of esketamine on postoperative rebound pain in patients undergoing total knee arthroplasty. Therefore, this trial is expected to fill an important gap in relevant fields and provide novel evidence for individualized pain management. Clinical Trial Registration http://www.chictr.org.cn, identifier ChiCTR2300069044.